2019
DOI: 10.1177/0890334419883203
|View full text |Cite
|
Sign up to set email alerts
|

“We Just Kind of Had to Figure It Out”: A Qualitative Exploration of the Information Needs of Mothers Who Express Human Milk

Abstract: Background Human milk expression, primarily by pump, is practiced by the majority of breastfeeding mothers in affluent countries. Existing literature is focused on determining prevalence and duration rates and the factors behind this trend. There is less research exploring mothers’ perspectives and experiences related to expression. Research aim To gather the experiential wisdom of mothers with a focus on their information needs and sources related to human milk expression. Methods Audiotaped interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…Dietrich Leurer et al found that participants who had ever expressed at all reported feeling negatively judged by healthcare providers for feeding expressed milk [ 33 ]. Some participants in the current study echoed similar sentiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietrich Leurer et al found that participants who had ever expressed at all reported feeling negatively judged by healthcare providers for feeding expressed milk [ 33 ]. Some participants in the current study echoed similar sentiments.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings by Strauch and colleagues that information sources included online parenting forums and one-way information websites and blogs but did not find any scholarly articles examining support for EE [ 35 ]. Similarly, Dietrich Leurer and colleagues also found that for women needing to express milk at all, milk expression information needs were often not addressed by healthcare providers [ 33 ]. With respect to EE, there are few information sources or classes available leaving many to do their own research from websites and online forums [ 36 ] which creates a vacuum of quality, reliable information.…”
Section: Discussionmentioning
confidence: 99%
“…Information on EP was often missing from prenatal classes, and there were no formal EP support programs, therefore, persons who exclusively pumped seeked information support, and guidance by doing their own research online and asking other parents on social media 9,35,37,42,49–51 . Healthcare providers often miss opportunities to give education and support on exclusive pumping 35,49 .…”
Section: Consequences Of Exclusive Pumpingmentioning
confidence: 99%
“…Information on EP was often missing from prenatal classes, and there were no formal EP support programs, therefore, persons who exclusively pumped seeked information support, and guidance by doing their own research online and asking other parents on social media 9,35,37,42,49–51 . Healthcare providers often miss opportunities to give education and support on exclusive pumping 35,49 . Education and support can help parents increase their knowledge and self‐efficacy around infant feeding and reinforce that breastmilk successfully can be fed in the absence of direct breastfeeding.…”
Section: Consequences Of Exclusive Pumpingmentioning
confidence: 99%
See 1 more Smart Citation